2021
DOI: 10.1186/s13024-021-00499-4
|View full text |Cite
|
Sign up to set email alerts
|

A panel of CSF proteins separates genetic frontotemporal dementia from presymptomatic mutation carriers: a GENFI study

Abstract: Background A detailed understanding of the pathological processes involved in genetic frontotemporal dementia is critical in order to provide the patients with an optimal future treatment. Protein levels in CSF have the potential to reflect different pathophysiological processes in the brain. We aimed to identify and evaluate panels of CSF proteins with potential to separate symptomatic individuals from individuals without clinical symptoms (unaffected), as well as presymptomatic individuals fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Recent proteomic studies have shown decreased levels of NPTXR in symptomatic genetic FTD, in all three genetic groups [ 45 ], and in sporadic bvFTD and PPA [ 46 ]. Two further studies additionally showed that NPTX2 was decreased in symptomatic mutation carriers in all three groups compared with controls using antibody-based approaches [ 47 , 48 ], and one of these studies showed that NPTX1 was decreased in C9orf72 and MAPT mutation carriers [ 48 ]. In our study, NPTX1 and NPTX2 were significantly decreased in all symptomatic groups, but NPTXR was only decreased in C9orf72 and GRN mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent proteomic studies have shown decreased levels of NPTXR in symptomatic genetic FTD, in all three genetic groups [ 45 ], and in sporadic bvFTD and PPA [ 46 ]. Two further studies additionally showed that NPTX2 was decreased in symptomatic mutation carriers in all three groups compared with controls using antibody-based approaches [ 47 , 48 ], and one of these studies showed that NPTX1 was decreased in C9orf72 and MAPT mutation carriers [ 48 ]. In our study, NPTX1 and NPTX2 were significantly decreased in all symptomatic groups, but NPTXR was only decreased in C9orf72 and GRN mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is possible that tau and TDP-43 mediated bvFTD have distinct spatiotemporal profiles of synaptic loss. This could be tested with studies using [ 11 C]UCB-J PET in preclinical models and people with genetically determined familial frontotemporal dementia (Van Der Ende et al ., 2020; Bergström et al ., 2021), or in due course by post mortem examination of those who have undergone PET. However, we suggest that synaptic loss is a mechanistic convergence point, present across diverse molecular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence for synaptic loss in frontotemporal dementia has been indirect, including reduced synaptic density in carriers of mutations associated with frontotemporal dementia (Malpetti et al ., 2021), abnormal synaptic markers in cerebrospinal fluid (Goetzl et al ., 2016; Van Der Ende et al ., 2020; Bergström et al ., 2021), and progressive frontotemporal hypometabolism that is disproportionate to atrophy, indicated by [ 18 F]FDG PET (Diehl-Schmid et al ., 2007; Malpetti et al ., 2019; Bejanin et al ., 2020; see Chételat et al ., 2020 for review). Recently, new tools to quantify synaptic density in vivo have been developed, including radioligands that bind selectively to synaptic vesicle protein 2A (SV2A) as an assay of synaptic density (Finnema et al ., 2016; Heurling et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The panel of proteins was further developed and narrowed in succeeding studies on various neurodegenerative disorders to investigate disease specificity. These studies focused on AD ( 15 , 16 ), PD ( 17 ), and FTD ( 18 , 19 ) amyotrophic lateral sclerosis (ALS) ( 20 )) and corticobasal degeneration (CBD) ( 21 ). In addition, one study investigated the associations of the selected panel proteins with the conventional CSF biomarkers for AD pathology on an asymptomatic cohort of asymptomatic 70-year-old individuals ( 22 ).…”
Section: Miriade Esr Processes In Biomarker Discovery and Developmentmentioning
confidence: 99%